Making partnerships work on the ground - Tumusiime, Emmanuel Mutebile (Springer, 2003)
For many years the Government of Uganda’s (GoU) development plans centred on the implementation of a series of three-year rolling Public Investment Plans (PIPs). PIPs contained many discrete projects in different sectors, which were nearly always wholly financed by external donors. The PIP system had a number of weaknesses: it fostered a piecemeal approach, encouraged little domestic ownership and lacked adequate coordination among the various stakeholders, resulting in duplication of efforts and inappropriate sequencing of projects to be implemented. To overcome these shortcomings, the government has been making concerted efforts to shift from a project-driven approach to the development of comprehensive, coordinated, sector-wide programmes and investment plans, involving the participation of all stakeholders in a genuine partnership. As part of this effort, the GoU is developing a Comprehensive Development Framework (CDF) process aimed at the modernisation of Uganda and the transformation of its society and eradicating mass poverty by the year 2017 (Wolfensohn, 1999). The Poverty Eradication Action Plan (PEAP) provides the basis for Uganda’s CDF process (Republic of Uganda, 1997a). The chapter outlines the institutional setting for the partnership process in Uganda and reflects on the conditions for continued improvement of the partnership process.
: experience in Uganda
Keywords: Civil Society; Shared Objective; Debt Relief; Virtuous Circle; Donor Support